The Role of Auditory Nonverbal Working Memory in Sentence Repetition for Bilingual Children with Primary Language Impairment - Ebert, Kerry Danahy (Int J Lang Commun Disord, 2014)
BACKGROUND: Sentence repetition performance is attracting increasing interest as a valuable clinical marker for Primary (or Specific) Language Impairment (LI) in both monolingual and bilingual populations. Multiple aspects of memory appear to contribute to sentence repetition performance, but nonverbal memory has not yet been considered. AIMS: The purpose of this study was to explore the relationship between a measure of nonverbal auditory working memory (NVWM) and sentence repetition performance in a sample of bilingual children with LI. METHODS & PROCEDURES: Forty-seven school-aged Spanish-English bilingual children with LI completed sentence repetition and nonword repetition tasks in both Spanish and English as well as an NVWM task. Hierarchical multiple linear regression was used to predict sentence repetition in each language using age, nonword repetition, and NVWM. OUTCOMES & RESULTS: NVWM predicted unique variance in sentence repetition performance in both languages after accounting for chronological age and language-specific phonological memory, as measured by nonword repetition. CONCLUSIONS & IMPLICATIONS: Domain-general memory resources play a unique role in sentence repetition performance in children with LI. Nonverbal working memory weaknesses may contribute to the poor performance of children with LI on sentence repetition tasks.